Lynch/Oz - Philippe, Alexandre O. ca. 20. Jh; Muratore, Robert 1968-; Nicholson, Amy; Ascher, Rodney ca. 20. Jh; Warner, Jack 1896-1981 (Dogwoof, 2022)
Victor Fleming's film Das zauberhafte Land (1939) is one of David Lynch's most enduring obsessions. This documentary goes over the rainbow to explore this Technicolor through-line in Lynch's work. [www.imdb.com]